2016
DOI: 10.5812/ijp.5413
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ Attitudes Toward Feeding Twin Babies in the First Six Months of Life: A Sample From Sakarya, Turkey

Abstract: BackgroundIt is stated in the literature that a mother’s breast milk is sufficient for more than one baby.ObjectivesThis descriptive study aimed to determine whether twin babies are breastfed during their first six months of life.Materials and MethodsWe studied the twin birth cases in a state hospital in Sakarya, Turkey between October 2011 and March 2013. The population of the study consisted of entire mothers who had delivered twins in the maternity ward of the hospital. The sample comprised 30 twins’ mother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Additionally, our findings showed that mothers having twins or triplets were less likely to exclusively breastfeed their children for 6 months and more. This is in line with a Turkish study where the prevalence of breastfeeding in twin babies was low [ 49 ]. Mothers of numerous babies believe they are poorly equipped to offer the best care for their children.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, our findings showed that mothers having twins or triplets were less likely to exclusively breastfeed their children for 6 months and more. This is in line with a Turkish study where the prevalence of breastfeeding in twin babies was low [ 49 ]. Mothers of numerous babies believe they are poorly equipped to offer the best care for their children.…”
Section: Discussionsupporting
confidence: 92%
“…Mothers of numerous babies believe they are poorly equipped to offer the best care for their children. Therefore, it is critical that mothers who are expecting twins or triplets be aware that their milk is sufficient; as well, they should be encouraged to breastfeed and should receive training on the benefits of breastfeeding [ 49 ]. Regarding determinants of complementary feeding, the introduction of solid, semi-solid or soft foods before the age of 6 months was much more common in boys than in girls.…”
Section: Discussionmentioning
confidence: 99%
“…that can be utilized during this period. Breastfeeding is more signi cant in multiple pregnancies, particularly since pre-term and low birth weight babies are frequently seen [19]. As a walking properly the other was still crawling with no sign of walking anytime soon.…”
Section: Reasons For a Chosen Daily Frequency Of Exclusivementioning
confidence: 99%
“…The breastfeeding rates in multiple pregnancies were reported to be between 24% and 79% in different cultures and at a different time (e.g., at 2 months and at discharge) intervals (1)(2)(3)(4). However, the rates of exclusive breastfeeding were reported as 3.3% in the 5 th month and 4.1% in the 6 th month (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…The use of breast milk is associated with a decreased incidence of complications however, many babies from multiple births cannot obtain the amount of milk they need due to the inexperience of mothers in breastfeeding, inadequate knowledge, and the belief that mothers have insufficient breast milk for two babies. The mothers of twins have sufficient potential to breastfeed their babies, but they need support from their families and health professionals (5).…”
Section: Introductionmentioning
confidence: 99%